Pengaruh Edukasi Pendekatan Spiritual Berbasis Video terhadap Kepatuhan Pembatasan Cairan Klien ESRD yang Menjalani Hemodialisa - Andri Kusuma Wijaya; Busjra Busjra; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of education with a video-based spiritual approach to compliance with fluid restriction or interdialysis weight gain in End Stage Renal Disease clients undergoing hemodialysis therapy. The research design used was pre-experimental one-group pretest-posttest. The results showed a difference in the average Interdialysis Weight Gain after education with a video-based spiritual approach (p value = 0.011;). While there is a proven relationship between family support (p value = 0, 047) with adherence to fluid restriction or interdialysis weight gain, while age (p value = 0.364), education level (p value = 0.949) has no relationship with adherence to fluid restriction or interdialysis weight gain. Conclusion, education with a spiritual approach can improve compliance with fluid restrictions in clients undergoing hemodialysis. Keywords: End Stage Renal Disease (ESRD), Spiritual Based Video